Field emission from laser cut CNT fibers and films. Issue 3 (22nd November 2013) - Fairchild, Steven B.; Bulmer, John S.; Sparkes, Martin; Boeckl, John; Cahay, Marc; Back, Tyson; Murray, P. Terrence; Gruen, Gregg; Lange, Matthew; Lockwood, Nathaniel P.; Orozco, Francisco; O'Neill, William; et al.
Abstract: Abstract : Field emission (FE) measurements are reported from carbon nanotube (CNT) fibers and laser-patterned free standing films fabricated by direct online condensation from a floating catalyst chemical vapor deposition reactor. Fiber and film cathodes showed stable emission in the 1–2 mA current ( I ) range at maximum cathode temperatures less than 1000 °C; film cathodes show localized heating at the triangular tips and higher maximum temperatures than the fibers. Fowler–Nordheim (FN) analysis indicated a change in the morphology of the emitters with increasing external electrical field ( E ext ). Fiber cathode I – E ext data are interpreted as FN emission from the fiber tip which is eventually limited by space-charge effects. At higher E ext, FN emission from the fiber sidewall occurs. The single fiber cathode stopped emitting abruptly when field induced self-heating effects became significant. For CNT films, self-heating effects can destroy a portion of the film, but FE can still occur from other areas.